The use of non-authoring software for the production of an interactive digital image map - Jaafar, Samsuddin (s.n, 2012)

(untitled)
Traditionally, maps are printed on papers as to aid users in carrying it with them. One of the drawbacks of paper base maps are that it comes with different paper sizes due to economic, portability and map theme issues. The advancement of ICT has increased the demands for digital maps to be used in handheld computers, PDAs, mobile phones, navigation equipments and web-publishing. Due to this, software developers have developed software that allows maps to be published digitally. These software are however expensive, specialized, proprietary and complicated for the normal layman to use. In Malaysia, efforts have been made to produce digital maps with different themes such as roads or tourists maps. Preliminary studies have shown that these maps are basically made from digitizing the paper maps and are value-added with information to suit the map themes. This method is basically changing the form of the paper maps from hardcopy to softcopy. The problem with these types of digital maps is that they have all the limitations of paper maps. One of the limitations of paper maps is that it uses symbols to depict ground data and a legend needs to be prepared to aid users in interpreting the data. Hence, the use of image map as compared to symbol based maps is an option in producing maps as image shows real ground features.